2019
DOI: 10.1136/gutjnl-2019-318593
|View full text |Cite
|
Sign up to set email alerts
|

Oral antibiotic use and risk of colorectal cancer in the United Kingdom, 1989–2012: a matched case–control study

Abstract: BackgroundMicrobiome dysbiosis predisposes to colorectal cancer (CRC), but a population-based study of oral antibiotic exposure and risk patterns is lacking.ObjectiveTo assess the association between oral antibiotic use and CRC risk.DesignA matched case–control study (incident CRC cases and up to five matched controls) was performed using the Clinical Practice Research Datalink from 1989 to 2012.Results28 980 CRC cases and 137 077 controls were identified. Oral antibiotic use was associated with CRC risk, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 26 publications
7
58
0
Order By: Relevance
“…On the other hand, the use of antibiotics in early childhood has been associated with increased colonic adenoma formation (a precursor lesion to CRC) in later life, suggesting that a dysbiotic microbiota is acquired and hold over a longer period of time [83][84][85]. In a recent study based on the Clinical Practice Research Datalink (CPRD), the use of oral antibiotics with anti-anaerobic activity has been associated with increased CRC risk in a dose-dependent fashion in the UK population, although the effects differed depending on the anatomical location, being greatest in the proximal colon [86]. In this regard, a systematic review and meta-analysis of observational studies was performed to assess whether the use of antibiotics was associated with the development of pre-cancerous or cancerous lesions in adults [87].…”
Section: Antibiotic-microbiome Link and Crc Riskmentioning
confidence: 99%
“…On the other hand, the use of antibiotics in early childhood has been associated with increased colonic adenoma formation (a precursor lesion to CRC) in later life, suggesting that a dysbiotic microbiota is acquired and hold over a longer period of time [83][84][85]. In a recent study based on the Clinical Practice Research Datalink (CPRD), the use of oral antibiotics with anti-anaerobic activity has been associated with increased CRC risk in a dose-dependent fashion in the UK population, although the effects differed depending on the anatomical location, being greatest in the proximal colon [86]. In this regard, a systematic review and meta-analysis of observational studies was performed to assess whether the use of antibiotics was associated with the development of pre-cancerous or cancerous lesions in adults [87].…”
Section: Antibiotic-microbiome Link and Crc Riskmentioning
confidence: 99%
“…Thus, almost all of the nonantibiotics mentioned above affect mitochondrial functions being either part of their modes of action or potential toxicities. Many antibiotics cause mitochondrial dysfunction, too, thus explaining their anti-neoplastic activities [30], or possibly promoting tumorigenesis [265][266][267][268], obesity [269], and psychiatric disorders [270,271]. Thus, antibiotics as well as non-antibiotics exert beneficial or detrimental antimitochondrial activities.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…Moreover, antibiotic-resistance was not always, but usually, associated with a significant economic burden resulting from (re-)admission to hospital, need for i.v.-administration, or even use of a less well tolerated antibiotic [390][391][392][393][394][395][396]. Antibiotics causing mitochondrial dysfunction may promote tumorigenesis [397][398][399][400], obesity [401], and psychiatric disorders [402,403]. Furthermore, this review has demonstrated that antibiotics may have an unpredictable impact on cell culture metabolism, gene expression and signalling cascades thus supporting a previous study entitled "are cell culture data skewed?"…”
Section: Phenicols Chloramphenicolmentioning
confidence: 99%